W miejsce wpisz brakujące wykładnik potęgi
a) 2^4*2^10=2
b) (-3)^3*(-3)*2=(-3)
c) (1,2)^4*(1,2)^-2=(1,2)
d) (-4,7)^2*(-4,7)=-4,7
e) a^2*a^*a-a
f) 2^5:2^3=2
g) (-1,8)^7:(-1,8)^5=(-1,8)
h) a^9:a^4=a



Odpowiedź :

Mokagd

Odpowiedź:

Szczegółowe wyjaśnienie:

Zobacz obrazek Mokagd
Zobacz obrazek Mokagd

[tex]a) \ 2^{4}\cdot2^{10} =2^{4+10}= 2^{14}\\\\b) \ (-3)^{3}\cdot(-3)^{2} = (-3)^{3+2} = (-3)^{5}\\\\c) \ (1,2)^{4}\cdot(1,2)^{-2} = (1,2)^{4-2} = (1,2)^{2}\\\\d) \ (-4,7)^{2}\cdot(-4,7) = (-4,7)^{2+1} = (-4,7)^{3}[/tex]

[tex]e) \ a^{2}\cdot a^{a-a} =a^{2}\cdot a^{0}=a^{2+0} = a^{2}\\\\f) \ 2^{5}:2^{3} = 2^{5-3} = 2^{2}\\\\g) \ (-1,8)^{7}:(-1,8)^{5} = (-1,8)^{7-5} = (-1,8)^{2} = (1,8)^{2}\\\\h) \ a^{9}:a^{4} =a^{9-4} = a^{5}[/tex]

Wyjaśnienie:

[tex]a^{m}\cdot a^{n} = a^{m+n}\\\\a^{m}:a^{n} = a^{m-n}[/tex]